The relationship between debt financing and firms' performance in Malaysia / Farisya Nadia Mohd Yunus - Mohd Yunus, Farisya Nadia (2017)
Debt financing is one of the most used methods to raise funds for expansionary or increase the market coverage by going global. In contrast with equity financing, debt financing is easily obtained from bank credit or other financial institutions offering credit plans. However, it is crucial for firms to assess the implications of the rise in debt level in relation to its profitability in order to ensure sustainability and growth of these firms. Present study sampled a total of 11 companies within the plantation sector in Malaysia to investigate the relationship between debt financing and firms' performance. Profitability is measured by the gross profit margin (GPM) while the independent variables used were total debt ratio (TDR), debt equity ratio (DER), interest coverage ratio (ICR), interest rate (INT) and inflation rate (INF). Results showed that T DR has an inverse impact on profitability whereas ICR has no role in explaining GPM. However, DER, INT and INF have a positive relationship with GPM. These findings will serve as a guide for firms that are deciding on opting for debt financing as it helps them in constructing the financial plan.